ANALISIS STRUKTUR DAN KONSEP TEOLOGIS YANG TERMUAT DALAM LONTAR TUTUR GONG BESI - I Putu Swana; Ni Luh Made Larasanti Komala Dewi (Widya Sandhi Jurnal Kajian Agama Sosial dan Budaya, 2023)
This study aims to analyze the structure and theological concepts contained in Lontar Tutur Gong Besi, so that it can be used as knowledge for students, university students and the general public in the field of Hindu literature. The study in this study used descriptive qualitative with a literature study approach with data analysis techniques on relevant documents, especially analysis on the Lontar Tutur Gong Besi document. Based on the results of the interpretation of the Gong Besi Speech Lontar, it can be explained that the structure of the Lontar Tutur Gong Besi consists of a formal structure and a content structure. The formal structure includes the use of Balinese kawi language with antithesis, association, repetition, and antonomasia styles. While the content structure includes the storyline from the beginning, core and closing. The theological concepts contained in the Lontar Speech of the Iron Gong include Henotheism, Animism, and Monotheism. The Lontar Tutur Gong Besi is Siwaistic in nature. This lontar is included in the Lontar Tattwa Religion group, the main discussion in this lontar relates to the omnipotence of Bhatara Dalem. Balinese people believe that Bhatara Dalem is a manifestation of Lord Shiva.